Inflation-target expectations and optimal monetary policy - Kapadia, S (University of Oxford, 2005)
In countries with credible inflation targeting, it seems plausible to suggest that instead of forming a rational expectation, some firms (inflation-targeters) might simply expect future inflation to always equal its target. This paper analyses the implications of this for optimal monetary policy in a standard new-Keynesian model. Under discretion, we show that if shocks have any persistence, inflation is more stable, loss is reduced, and the optimal policy frontier is improved as the proportion of inflation-targeters increases. Considering the commitment case, we show that the benefits of commitment are diminished (stabilisation bias is reduced) in the presence of inflation-targeters, but overall loss is still reduced relative to the rational expectations benchmark for plausible parameter values and mild persistence in the shock. Taken together, these results formally illustrate how policies which encourage expectations anchoring may be beneficial for the economy.